Poetic force poetry after Kant - McLaughlin, Kevin 1959- (Meridian: crossing aesthetics, 2014)
Ur-ability : force and image from Kant to Benjamin -- Hölderlin's peace -- Poetic reason of state : Baudelaire and the multitudes -- Arnold's resignation -- Epilogue : making room for reason